Dioctofimose canina no Rio Grande do Sul. Descrição de quatro casos - Graça, Dominguita Lühers; Copello, Romer Arapé; Santos, Murilo Nogueira dos (Revista do Centro de Ciências Rurais, 2008)
São relatados quatro casos de dioctofimose canina em Santa Maria, Rio Grande do Sul, Brasil. Em três deles, o Dioctophyme renale parasitava o rim direito; no quarto, a cavidade abdominal. Em nenhum caso houve diagnóstico clínico.AbstractFour cases of canine dioctophymiasis are related in Santa Maria, State of Rio Grande do Sul, Brasil. In three of them the affected viscus was the right kidney; in the fourth one, the worm was located in the abdominal cavity. No one was clinically diagnosed.